Eksplorasi Strategi Guru Dalam Meningkatkan Maharah Al-Kalam Bagi Siswa: (Studi di Madrasah Aliyah Bolaang Mongondow Utara) - Moh. Sultan Dama (LP2M IAIN Sultan Amai Gorontalo, 2019)
Some problems are found that: (1) students are not able to understand Arabic vocabulary; (2) some students are graduates of public schools, this causes difficulties for students to speak Arabic; (3) lack of facilities such as textbooks and the absence of language laboratories. Based on the problems faced above, this study aims to find out what strategies are carried out by the teacher in improving the ability of the students in speaking Arabic. The research method used is a descriptive qualitative. The results of the study show that the teachers combine various methods and strategies in the process of learning Arabic such as Qowaid, Nahwu Sharf and lectures. The teachers also guide extracurricular activities through the Al-Qur'an reading and writing park formed by the school. This place accommodates students to learn, to read and also expedite the reading of the Qur'an.